Digital Learning to Develop Teaching Media Applications - Mustamin; Retyana Wahrini (International Journal of Educational and Life Sciences, 2024)
Digital transformation in learning media has become an increasingly relevant topic in the world of education, especially in the context of increasing student engagement and skills. Education plays a part in raising the caliber of HR-owned resources. The purpose of this study is to develop a teaching media application in the Multimedia Learning course. The research and development approach, or R&D, is the methodology employed in this process. Based on an industry-based development approach, research and development is conducted to create goods and procedures that are subsequently thoroughly tested in the field, assessed, and improved to satisfy specific standards for efficacy, quality, and standards. It has been demonstrated that using interactive multimedia-based learning materials in multimedia courses enhances students' conceptual understanding. The stages of developing this interactive learning media product are through validation tests and large group tests, and the final stage is implementation in learning. It may be said that students' interest in learning has enhanced when interactive learning materials are used in the Multimedia Learning course.